Cancellation of Deed of Sale and Purchase of Land Rights and Deed of Granting Mortgage Based on Court Decision - Devendra Dovianda Priyono (Social Science Studies, 2021)
This study is entitled "Cancellation of Deed of Sale and Purchase of Land Rights and Mortgage Deed Based on Court Decision". The first of this research aims to find out how the precautionary principles applied by PPAT in making the Deed of Sale and Purchase of Land Rights and the Mortgage deed Rights and the second is to find out and analyze the basis of legal considerations used by judges in deciding cases of cancellation of PPAT Deeds. This type of research in legal research is empirical, using a case approach that is supported by interviewing informants. Data analysis in this legal research uses qualitative analysis. The resource persons in this legal research are PPAT in Yogyakarta City, Bantul Regency and Kulonprogo Regency. Based on the results of the first research, that PPAT in making the Deed of Sale and Purchase of Land Rights and the Mortgage deed Rights must apply the precautionary principle as regulated in Article 22 of Government Regulation Number 37 of 1998 that the PPAT Deed must be read / explained its contents to the parties by attended by at least 2 (two) witnesses before being signed immediately by the parties, witnesses and PPAT, PPAT is obliged to apply the prudential principle to avoid problems that arise and harm the parties and to prevent the PPAT Deed being canceled and becoming not legally enforceable. Second, the basis for legal considerations used by the judge to cancel the PPAT deed was because the buyer committed tort and abuse of circumstances against elderly sellers who were sick, lived alone and could not read and write and were lied to by the Buyer's words.